Biofilm formation and surface characteristics of conventional glass ionomer, resin-modified glass ionomer, and GC gold hybrid restorative material - Amutha Mathu Vimala Soorya; Vishnu Rekha Chamarthi; Mahalakshmi Krishnan; Dhanraj Kalaivanan; Santham Krishnamoorthy; Sumaiyya Saleem; Sai Sarath Kumar Kothimbakkam; Santhosh Priya Appiya Krishnan Ramnath Babu (Journal of Dental Materials and Techniques)
Objective: The present study aimed to evaluate the surface roughness, microhardness, and biofilm formation of conventional glass-ionomer cement (GIC) and two GIC-based restorative materials.Methods: Twenty-four samples were prepared from each of the following restorative materials: Group 1) GIC, Group 2) resin-modified glass-ionomer cement (RMGIC), and Group 3) GC Gold Hybrid restorative material. The surface roughness and microhardness of specimens were evaluated using a surface profilometer and a Vickers microhardness tester, respectively. Half of the samples in each group were exposed to Streptococcus mutans suspension and the other half to Streptococcus oralis suspension. The bacterial colonies were counted using a digital colony counter. Data were compared using the Kruskal Wallis and Wilcoxon signed rank tests (α=0.05).Results: The surface roughness and microhardness values were significantly different among the groups (P = 0.001). RMGIC showed significantly lower surface roughness and significantly higher microhardness among the groups (P<0.05). There was a significant difference in S. mutans biofilm formation among the groups (P< 0.001), but S. oralis biofilm was not significantly different (P=0.063). GC Gold Hybrid had a significantly higher S. mutans biofilm formation compared to other groups (P<0.05). The formation of S. oralis biofilms was significantly higher than that of S. mutans biofilms in all materials (P < 0.05).Conclusions: RMGIC had the most favorable surface properties among the groups. GC Gold Hybrid had a higher bacterial adhesion and less favorable surface properties, which might increase the rate of secondary caries around the restoration.